Why are Patient Portals Important in the Age of COVID-19? Reflecting on Patient and Team Experiences From a Toronto Hospital Network. (July 2022) - Lo, Brian; Charow, Rebecca; Laberge, Sarah; Bakas, Vasiliki; Williams, Laura; Wiljer, David
The COVID-19 pandemic has changed how care is being delivered in Canada. With conventional in-person care being transitioned to virtual care, the approach that patients are able to engage and access their care has dramatically changed. At the University Health Network (UHN), which is Canada's largest academic and teaching hospital network, we expanded the myUHN Patient Portal in 2017 after its early adopter phase to enable patients and family members to view parts of their clinical notes and test results. As the pandemic progressed, we observed high adoption of myUHN to support virtual care and rapid delivery of COVID-19 test results in real time. In this article, we share and reflect on our experience of adapting myUHN to support the demands of the pandemic, including portal adoption outcomes across multiple waves of the pandemic, the impetus for increased patient experience staff dedicated for myUHN support, and patients' perceptions of the value of the portal and virtual care. Based on these reflections, we outline our perspectives on the future role of patient portals to support patient care and experience in a post-pandemic environment.